The Use of Video Media in an Effort to Improve the Learning Outcomes of Civics in Class II Students of SDN 4 Jalatunda - Rusmiati, Rusmiati (Universitas Sebelas Maret, 2020)
Based on the results of observations, it shows that Civics learning is still carried out conventionally where teachers still use learning media that is limited to textbooks. This causes students to act less in the learning process and the learning outcomes obtained are low. Focusing on the problem, this study aims to improve planning, implementation and assessment of Civics learning using video media. This classroom action research uses qualitative and quantitative approaches. In practice, the study, which consisted of three cycles, was carried out collaboratively with fellow teachers. The research was conducted in the odd semester of the 2020/2021 school year at SDN 4 Jalatunda with the research subjects being all grade II students. The research data were collected through observation, interviews, field notes, documentation and tests. The results of data analysis indicate that the use of video media can improve student learning outcomes in class II Civics learning at SDN 4 Jalatunda. This can be seen from (1) students' cognitive learning outcomes have increased from an average value of 71.43 in the first cycle to 85.71 in the second cycle and 92.86 in the third cycle (2) the affective domain has increased from an average value of 64 , 29 in cycle I to 82.14 in cycle II and 92.86 in cycle III, and (3) in psychomotor increased from an average value of 72.32 in cycle I to 80.81 in cycle II and 89.29 in cycle cycle III. Seeing the results of this study, classroom action research in the use of video media in Civics learning needs to be applied and developed in order to improve the quality of education in the future.